Open source requirements engineering - Paech, Barbara; Reuschenbach, Bernd (Proceedings 14th IEEE International Requirements Engineering Conference, 2006)
This paper describes an experience in requirements engineering for an open source E-learning tool selection. The process meets the challenges of software selection such as the intertwining of requirements acquisition and product evaluation, the level of detail or the information collection. In addition, it is user-driven and just-in-time. Despite their time constraints the stakeholders were able to contribute throughout the whole process. The decisions and the effort for preparing these decisions were postponed to the latest possible point in time. This process seems also suitable for open source software development.